Congestion avoidance routing for MANETs. (10th June 2014) - Ho, Yao Hua; Chen, Meng Chang; Chao, Han–Chieh
In a mobile ad hoc network (MANET), communication connections need to adapt to frequent and unpredictable topology changes. Early solutions focused reconnecting a broken link quickly with a low overhead; however, this strategy cannot cope with a high mobility environment. For high mobility environments, greedy techniques rely on any mobile hosts along the general direction of the destination node to forward data packets. However, the greedy approach suffers from packet loss because the packet forwarding policy does not consider traffic congestion along the route or the direction. In this paper, we propose a congestion avoidance routing (CAR) technique for two greedy protocols, connectionless approach (CLA) and contention–based forwarding (CBF), to address the packet loss problem by rerouting packets dynamically to avoid traffic congestion. To demonstrate the improvement, we present extensive simulation results to show the proposed techniques can prevent the occurrence of contention areas and significantly outperform existing techniques.